(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Background: the green synthesis methods of nanoparticles have attracted great attention. Zinc oxide (ZnO) is considered one of the most studied nanoparticles due to its nontoxic nature and low cost, and iron oxide (FeO) nanoparticles due to their superparamagnetic properties. In this study, ZnO, FeO and Fe-doped ZnO NPs were synthesized from leaf extract of Leucaena leucocephala L. Methods: we have been using green methods in the synthesis of this nanoparticles by preparing plant extract and then preparing the Zno, FeO, Fe-doped ZnO nanoparticles and characterizing these nanoparticles by several methods to confirm the formation of nanoparticles. Result: the green synthesis of the ZnO, FeO, doped Fe-ZnO nanoparticles was confirmed by AFM and further characterized by UV-Vis and EDX. UV-VIS showed peak at 290nm (ZnO), 190nm(FeO), 300nm Fe-ZnO Nps. AFM revealed an average diameter of ZnO 40.67nm, FeO was 42.44nm, while doped Fe-Zno was 122.8nm. EDX confirms the formation of ZnO, FeO, doped Fe-ZnO nanoparticles. this green synthesis method was observed to be ecofriendly and cost-effective method in the synthesis of ZnO, FeO, doped Fe-ZnO nanoparticles by Leucaena leucocephala L. Conclusion: The result confirms the potential of Leucaena leucocephala L for the synthesis of the ZnO, FeO,-doped Fe-ZnO nanoparticles in simple, cost-effective, easy, and ecofriendly methods.